Washington, D.C - Furman, Elina; Flynn, Margaret E; Matusevich, Melissa N (New York Children's Press, 2002)
Describes the geography, history, government, people, and places of Washington, D.C
Includes bibliographical references (p. 76) and index
Hurg
5
Keywords: Washington -- Juvenile literature; Washington